Building partnerships in education through a story-tool based intervention: Parental involvement experiences among families with Roma backgrounds - Moreira, Tânia; Martins, Juliana; Silva, Cátia; Berrocal de Luna, Emilio; Martins, Joana; Moreira, Daniela; Rosário, Pedro (Frontiers in Psychology, 2023)
Introduction School educators are likely to explain the poor educational trajectories of students with Roma backgrounds related to the lack of parental support and interest in children’s education. Aiming to understand further the patterns of Roma group’s parental involvement in children’s school life and their engagement experiences in school-related activities, the current research set an intervention supported by a culturally sensitive story-tool. Method Grounded in the intervention-based research framework, 12 participants (i.e., mothers) from different Portuguese Roma groups participated in this study. Data was collected through interviews conducted pre-and postintervention. Eight weekly sessions were delivered in the school context, using a story-tool and hands- on activities to generate culturally significant meanings regarding attitudes, beliefs, and values toward children’s educational trajectories. Results Through the lens of acculturation theory, data analysis provided important findings under two overarching topics: patterns of parental involvement in children’s school life and participants’ engagement in the intervention program. Discussion Data show the distinct ways Roma parents participate in children’s education and the relevance of mainstream contexts providing an atmosphere likely to build collaborative relationships with parents to overcome barriers to parental involvement.